2016
DOI: 10.1097/01.jhq.0000462674.09641.72
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Readmission Risk Factors for Patients With Chronic Conditions

Abstract: Evidence indicates that the largest volume of hospital readmissions occurs among patients with preexisting chronic conditions. Identifying these patients can improve the way hospital care is delivered and prioritize the allocation of interventions. In this retrospective study, we identify factors associated with readmission within 30 days based on claims and administrative data of nine hospitals from 2005 to 2012. We present a data inclusion and exclusion criteria to identify potentially preventable readmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…First, the C statistic of 0.70 is comparable to the C statistic reported with other models developed for diabetes patients (8,10,26). Likewise, a systematic review identified 7 readmission risk prediction models not restricted to diabetes that could be used to identify high-risk patients during a hospitalization, with C statistics ranging from 0.56 to 0.72 (29).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…First, the C statistic of 0.70 is comparable to the C statistic reported with other models developed for diabetes patients (8,10,26). Likewise, a systematic review identified 7 readmission risk prediction models not restricted to diabetes that could be used to identify high-risk patients during a hospitalization, with C statistics ranging from 0.56 to 0.72 (29).…”
Section: Discussionsupporting
confidence: 69%
“…Although discharge within 90 days prior to admission has not specifically been reported by other groups, prior hospitalizations and emergency department visits have been shown to predict 30-d readmission risk (7,10,26). Likewise, diabetes complications; preadmission insulin use; and admission serum hematocrit, sodium, and creatinine have not been previously identified as predictors of 30-d readmission, but several other groups have demonstrated that comorbidity burden is associated with readmission risk (7,8,10,26,27). In contrast, anemia has been previously reported (28).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although discharge within 90 days prior to admission has not specifically been reported by other groups, prior hospitalizations and emergency department visits have been shown to predict 30d readmission risk [25, 22, 30]. Likewise, diabetes complications have not been previously isolated in published studies as predictors of 30d readmission, however several other groups have demonstrated that comorbidity burden is associated with readmission risk [23, 25, 22, 31, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, diabetes complications have not been previously isolated in published studies as predictors of 30d readmission, however several other groups have demonstrated that comorbidity burden is associated with readmission risk [23, 25, 22, 31, 30]. In addition, educational attainment has not been previously associated with 30d readmission.…”
Section: Discussionmentioning
confidence: 99%